The HDAC6 Inhibitor Tubacin Induces Release of CD133+ Extracellular Vesicles From Cancer Cells. Issue 12 (31st May 2017) - Chao, Olivia S.; Chang, Tim C.; Di Bella, Maria A.; Alessandro, Riccardo; Anzanello, Fabio; Rappa, Germana; Goodman, Oscar B.; Lorico, Aurelio
ABSTRACT: Tumor‐derived extracellular vesicles (EVs) are emerging as an important mode of intercellular communication, capable of transferring biologically active molecules that facilitate the malignant growth and metastatic process. CD133 (Prominin‐1), a stem cell marker implicated in tumor initiation, differentiation and resistance to anti‐cancer therapy, is reportedly associated with EVs in various types of cancer. However, little is known about the factors that regulate the release of these CD133 + EVs. Here, we report that the HDAC6 inhibitor tubacin promoted the extracellular release of CD133 + EVs from human FEMX‐I metastatic melanoma and Caco‐2 colorectal carcinoma cells, with a concomitant downregulation of intracellular CD133. This effect was specific for tubacin, as inhibition of HDAC6 deacetylase activity by another selective HDAC6 inhibitor, ACY‐1215 or the pan‐HDAC inhibitor trichostatin A (TSA), and knockdown of HDAC6 did not enhance the release of CD133 + EVs. The tubacin‐induced EV release was associated with changes in cellular lipid composition, loss of clonogenic capacity and decrease in the ability to form multicellular aggregates. These findings indicate a novel potential anti‐tumor mechanism for tubacin in CD133‐expressing malignancies. J. Cell. Biochem. 118: 4414–4424, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Treatment of cancer cells with the HDAC6 inhibitor tubacin increased the release of extracellular vesicles (EVs) that contain CD133. This tubacin‐induced EV release was associated with changes in cellular lipid composition, loss of clonogenic capacity, and decrease in the ability to form multicellular aggregates. These findings may constitute a potentially novel anti‐cancer approach.